2022
DOI: 10.1007/s10021-022-00764-7
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Effects of Climate, Land Use, and Insects on Dung and Carrion Decomposition

Abstract: Land-use intensification and climate change threaten ecosystem functions. A fundamental, yet often overlooked, function is decomposition of necromass. The direct and indirect anthropogenic effects on decomposition, however, are poorly understood. We measured decomposition of two contrasting types of necromass, rat carrion and bison dung, on 179 study sites in Central Europe across an elevational climate gradient of 168–1122 m a.s.l. and within both local and regional land uses. Local land-use types included fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…Moreover, in Harris et al (2019) and Williams et al (2014), increasing temperatures and low precipitation, respectively, were found to potentially decrease the abundance and diversity of some ground‐dwelling beetles. In a previous study, Englmeier et al (2022) found a hump‐shaped pattern of dung removal rates along an elevational gradient, indicating that environmental conditions at intermediate altitudes are more beneficial for dung beetles than in lowlands. Therefore, we assume that climate warming might exacerbate the access to and decomposition of dung by insects, which could explain the potential future emigration of coprophilic beetles to cooler regions as observed by Menéndez et al (2014).…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, in Harris et al (2019) and Williams et al (2014), increasing temperatures and low precipitation, respectively, were found to potentially decrease the abundance and diversity of some ground‐dwelling beetles. In a previous study, Englmeier et al (2022) found a hump‐shaped pattern of dung removal rates along an elevational gradient, indicating that environmental conditions at intermediate altitudes are more beneficial for dung beetles than in lowlands. Therefore, we assume that climate warming might exacerbate the access to and decomposition of dung by insects, which could explain the potential future emigration of coprophilic beetles to cooler regions as observed by Menéndez et al (2014).…”
Section: Discussionmentioning
confidence: 91%
“…In most cases, warmer and more humid conditions are associated with faster decomposition (Moore et al., 2004), as shown, for example, for deadwood (Seibold et al., 2021) and carrion (Benbow et al., 2013, 2019; Probst et al., 2020). However, within a temperate zone, elevation had a positive effect on rats carcass decay rates during summer, which was explained by more humid conditions and less mummification (Englmeier et al., 2023). For a carrion species with a larger body size, as in our study, the effect of elevation gradient is less well‐studied.…”
Section: Discussionmentioning
confidence: 99%
“…Here, beetle community composition was predictive of the decay process, supporting previous work showing that beetle community composition, affected by the mean annual temperature, significantly affected mice carrion decomposition (Farwig et al., 2014). An insect exclusion experiment found clear effects of reduced rat carcass decay when insects were excluded (Englmeier et al., 2023). Therefore, the occurrence of specific taxa, for example, Diptera or Coleoptera, significantly affects carcass decomposition and PMI estimates (Kadlec et al., 2019; Pechal, Benbow, et al., 2014; Popescu et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decomposer and scavenger communities depend on the carcass remains of large herbivores as a food resource and breeding substrate, while other decomposer species depend on dung for survival ( Nichols et al 2008 , Butterworth et al 2022 ). These decomposers play a key role in maintaining biodiversity and ecosystem functions and services such as nutrient and energy cycling ( Barton et al 2013 , Englmeier et al 2022 ). The sudden removal of a large number of herbivore species from an ecosystem may have unintended negative consequences on dependent species, which in turn could have bottom-up effects on the food web and broader ecosystem function ( Iida et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%